A proposed parish guidance program for St. John the Baptist, Tagig, Tipas - De Leon, Francisco M. (Animo Repository, 1973)
v. 1. This study seeks to determine the role a guidance program can play in the parish of St. John the Baptist, Tagig, Rizal. It also determines the services the parish priest can offer the people through an organized guidance program. The method of research used in this paper was the deliberative or reflective-thinking approach. Background data were gathered from the survey of Action Leaven and from the personal experiences of the researcher in the parish. The proposed guidance service was categorized into two : those which help man's external development like the medical and health service, community building service, and the information service, and those which help man's internal development like the counseling service. In the proposed program, emphasis was given on the counseling and community building service. The line and staff organization was recommended and the roles of the administrator and the different professional guidance personnel were delineated. An actual scientific survey of the different needs of the people was needed before the program can be implemented so that modifications of the proposed program can be made if the survey showed any need for them. A guidance program in a parish would help the community, the family, and the individual resolve their conflicts into a development rather than a maladjustment. A functional guidance program in St. John the Baptist would open the door for other parishes to follow. Organization of guidance programs in other parishes would help the Church in her mission to serve in the development of the total man. v. 3. This case study was conducted to demonstrate how, through a counseling relationship with Olie, the counselor-trainee fulfilled three major specific objectives of the counselor-training program : 1) to demonstrate a counseling style with which the counselor-trainee is comfortable and in which he can support his techniques by knowledge of underlying theory and practice 2) to demonstrate interviewing and observational skills by conducting various interviews and compiling a detailed behavioral descriptions and 3) to select appropriate appraisal instruments and/or techniques. In order to gather the necessary information on the counselee, the following techniques were used : 1) the counselor conducted interviews with the counselee, his lola, and the nun who referred the counselee to the counselor. These interviews were all conducted face to face general leads like clarification, interpretation, summary-clarification, and probing were used in these interviews. Besides these interviews, the counselor joined the relatives of the counselee in their small talks whenever invited for a merienda by them. In these small talks the significant others of the counselee often revealed what they thought and expected of the counselee. 2) Intelligence and personality tests were administered to the counselee. They were the Weschler Adult Intelligence Scale (WAIS), Hish School Personality Questionnaire (HSPQ), Draw-a-Person test, Bender Gestalt, Psycholexicon, and the Sacks Sentence Completion Test (SSCT) in Pilipino. After presenting Olie's biographical data and his personality as shown by the different personality tests, three of his problems were identified : 1) the evening prayer problem, 2) the money-problem, and 3) the communication problem. With the approval of the counselee, the counselor used some behavioral counseling techniques to meet the three problem areas: simple agreement, role shift, behavior contract, and simulation. The counselees relevant behaviors, however, did not change because he had not yet identified hi